Gluing Living Bone Using a Biomimetic Bioadhesive: From Initial Cut to Final Healing - Procter, Philip; Hulsart-Billström, Gry; Alves, Antoine; Pujari-Palmer, Michael; Wenner, David; Insley, Gerard; Engqvist, Håkan; Larsson, Sune (Frontiers in Bioengineering and Biotechnology, 2021)
Fractures due to osteoporosis is a growing issue due to the increase of osteoporosis worldwide. High reoperation rates in osteoporotic fractures calls for investigation into new methods in improving fixation of osteoporotic bone. A novel ex-vivo bone core assay for assessing the strength of a recently developed bone bioadhesive, was evaluated in-vivo in a murine animal model at 0,3,7,14,28 and 42 days. Histology and micro-CT were obtained at all time points and the mean peak pull-out force was assessed on days 0 to 28. The adhesive provided immediate fixation to cancellous bone, and up to 50% of physiological strength throughout healing. The mean peak bone core pull-out force gradually decreased from 6.09N (σ 1.77N) at day 0, to a minimum of 3.09N (σ 1.08N) at day 7, recovering to 6.37 N (σ 4.18N) by day 28. The corresponding fibrin (Tisseel) control mean peak bone core pull-out characteristic was 0.27 N (σ 0.27N) at day 0, with an abrupt increase from 0.37N (σ 0.28) at day 3 to 6.39N (σ 5.09N) at day 7, continuing to increase to 11.34 N (σ 6.5N) by day 28. The bone cores failed either through core pull-out or by the cancellous part of the core fracturing. Overall, the adhesive does not interrupt healing, no pathological inflammation with rapid resorption, and replacement with new tissue, vasculature, and marrow. Initially the adhesive bonded the bone core to the femur and over time the adhesive was replaced by bone of equivalent quality and quantity to the original bone. At the 42-day time point 70% of the adhesive in the cancellous compartment had been replaced and 50% in the cortical compartment. The adhesive out-with the bone shell was metabolised by cells that are only removing the material with no additional bone formation. It is concluded that the adhesive is not a physical and biochemical barrier as the bone heals through the adhesive and is replaced by normal bone. This adhesive composition meets many of the clinical unmet needs expressed in the literature and may, after further preclinical assessments, have potential in the repair of bone and osteochondral fragments.